Could the Construction of Sustainable Development Pilot Zones Improve the Urban Environment Efficiency in China?. (12th March 2020) - Ma, Junxia; Zhang, Zilong; Lu, Chenyu; Xue, Bing
Abstract : As the forerunner and policy test field of the sustainable development, the sustainable development pilot zones are an important strategy for China to explore the mechanism and model of the coordinated development of human and land in different regional units. However, the impact of sustainable development pilot zones, especially on the improvement of environmental efficiency, needs to be assessed. In this paper, 187 prefecture-level cities in China were taken as samples (22 sustainable development pilot zones and 165 nonpilot ones). Firstly, the environmental efficiency of 187 prefecture-level cities between 2006 and 2016 was measured by data envelopment analysis (DEA). Then, the effect of construction of sustainable development pilot zones on environmental efficiency was assessed using the difference-in-difference (DID) model. The assessment results were further verified by propensity score matching with difference-in-difference (PSM-DID). In addition, the impact mechanism of construction of the sustainable development pilot zones on the environmental efficiency was discussed. Results show that the environmental efficiency of sustainable development pilot zones is 27.7∼31.7% greater than that of nonsustainable one, which is mainly attributed to the environmental regulation and industrial structure adjustment.